Digital Marketing Strategy Analysis “Lagoon Avenue Mall” Towards Sustainable Development Goals 5 Target - Ndini, Ayu Sekar (Jurnal Wanita dan Keluarga, 2024)
This study examines the digital marketing strategy of Lagoon Avenue Mall Sungkono Surabaya in promoting Sustainable Development Goal 5 (SDG 5), focusing on women's empowerment. Employing a qualitative approach, the research delves into the strategies implemented by the mall's internal team and insights from community partners and event organizers who have collaborated with the mall. The combination of internal and external perspectives provides a comprehensive view of the digital marketing efforts and the challenges faced in achieving SDG 5. The findings indicate that while Lagoon Avenue Mall has succeeded in targeting specific market segments and developing mall-based events, several areas require enhancement. Challenges include imprecise audience targeting, inadequate campaign performance evaluation, lackluster content, and low user engagement. Administrative issues related to rental contracts, uncertainty about non-financial collaboration benefits, and competition from other malls also pose significant obstacles. The study offers actionable recommendations for improving the digital marketing strategy to better support SDG 5 goals, particularly in empowering women. By refining these strategies and addressing the identified challenges, Lagoon Avenue Mall can more effectively contribute to sustainable development and meet the objectives of the SDG agenda.